GLASS-CERAMICS: THEIR PRODUCTION FROM WASTES - Rees D Rawlings (Jurnal Sains Materi Indonesia, 2003)
GLASS-CERAMICS: THEIR PRODUCTION FROM WASTES. Glass-ceramics are fine, polycrystalline materials that are produced by the controlled crystallization (devitrification) of a glass. The fundamental principles of the crystallization are presented briefly and the various processing methods for glass-ceramics described in light of these fundamental principles. Two examples of the production of glass- ceramics from wastes are discussed in detail; the wastes are slag from steel production and fly ash from incineration.